Enhancing The Performance of Community-Based MSMEs Through Multi-Actor Ecosystem Governance: Evidence from MACTOR Analysis - Anggraini, Raden Isma; Maarif, Mohammad Syamsul; Asikin, Zenal; Sukmawati, Anggraini (International Journal of Accounting and Economics Studies, 2025)
Community-based Micro, Small, and Medium Enterprises (MSMEs) are instrumental in promoting inclusive economic development, particularly in developing countries where access to formal employment and capital is often limited. Despite their potential, these enterprises frequently face challenges such as fragmented support systems, low digital readiness, and weak integration with formal policy frameworks. This study aims to examine how multi-actor ecosystem governance can enhance the performance of community-based MSMEs by identifying the influence, roles, and convergence of various institutional and community actors, while integrating the dimensions of intellectual capital. This research employed the MACTOR (Matrix of Alliances and Conflicts: Tactics, Objectives, and Recommendations) method to map and analyze the strategic positions of key actors against strategic objectives derived from literature synthesis and stakeholder interviews. The analysis focused on direct and indirect influence, convergence-divergence relationships, strategic alliances, and actor role typologies in the MSMEs development ecosystem. The results indicate that government institutions, particularly the Ministry of SMEs, local government, and technology companies, hold the highest influence within the ecosystem and align strongly on objectives related to institutional support, financial access, and digital transformation. Educational institutions and NGOs contribute significantly to relational and structural capital, facilitating knowledge sharing and community engagement. Conversely, traditional cooperatives and informal groups demonstrate lower influence and alignment, highlighting areas for targeted capacity-building. Actor convergence mapping identified four clusters with shared priorities, enabling strategic coalition-building across institutional and community actors. These findings offer a novel framework for understanding the dynamics of actor collaboration in community-based MSMEs ecosystems. By integrating intellectual capital with ecosystem governance through MACTOR analysis, this study provides actionable insights for policymakers, development agencies, and community leaders. The research underscores the importance of strategic foresight, actor alignment, and inclusive interventions in promoting resilient and sustainable MSMEs growth.